Evaluation and Comparison of Patterns of Maternal Complications Using Generalized Linear Models of Count Data Time Series - Odhiambo, Collins; Kinoti, Freda (International Journal of Statistics in Medical Research, 2019)
Studying patterns of maternal complications is critical before, during and after childbirth. However, there is limited information on comparative trends of different maternal complications, particularly, in a resource-limited setting. In this study, we fit six different types of maternal complications namely ante-partum haemorrhage (APH), eclampsia, obstructed labour, post-partum haemorrhage (PPH), ruptured uterus and sepsis to time series generalized linear model. We systematically compare the performance of the model in light of real data by checking its flexibility and serial correlation and the conditional distribution. We then, compute model fitting, assessment and prediction analysis for each maternal complication. Additionally, we provide a comparative review of the results by assessing the effect of intervention 1: basic emergency obstetric and new-born care (BEmONC) and intervention 2: comprehensive emergency obstetric and new-born care (CEmONC) services on trends in maternal complications. Results show that women with APH, eclampsia and obstructed labour at the time of delivery are significantly high. Maternal complication did not statistically vary by counties. The results of count GLM for APH showed presence of Intervention1 (BEmONC) reduces APH by a factor -0.189 (LCI =- 0.298, UCI= -0.0805) while CEmONC was not statistically significance. Similar inference is registered by PPH i.e. Intervention1 (BEmONC) is -0.17 (LCI =-0.258, UCI= - 0.082) while CEmONC remains insignificant. This can be interpreted to mean that public health facilities only require the basic minimum (BEmONC) infrastructure to cub APH and PPH. Mothers with sepsis and eclampsia were significantly more likely to experience maternal and perinatal deaths when delivering at facilities that lack BEmONC. Caregivers, who perform obstetric and maternal care, need be alert of maternal complications associated with PPH and obstructed labour. Introduction of BEmONC and CEmONC packages in maternal and neonatal clinics improved performance of caregivers in reducing maternal and pediatric complications and mortality.